The Promise of Higher Education Essays in Honour of 70 Years of IAU - van't Land, Hilligje; Corcoran, Andreas; Iancu, Diana-Camelia (Springer Nature, 2021)
This book is a collection of short essays, accessible through open access, which takes the interested reader on a tour across the global higher education landscape. It addresses pertinent themes and challenges in higher education. To mark the 70th anniversary of the International Association of Universities (IAU) and its role in higher education since 1950, experts from around the world share their insights into higher education's recent past, present and future. The book is divided into six parts: Part I - "70 years of Higher Education Cooperation and Advocacy" looks back at key events in IAU's history, its mission and significant activities over time, and remarks on the current global context informing its quest to promote academic partnerships and solidarity on a global scale. Part II - "Facilitating International Cooperation" provides for different perspectives on the transformation of the internationalisation of higher education and the contribution of higher education to international cooperation. Part III - "Coding the Values" debates the values upon which higher education was, is and will have to be built to provide for a democratic and inclusive society. Part IV - "The Changing Landscape" analyses various aspects of the transformation of higher education in an evolving context across the globe. Part V - "The Promise of Education" reflects on the role of higher education, its ideals and shortfalls and what it must do to stay true to its promise to help shape our societies. Part VI - "Opening up - The Future of Higher Education" focuses on future scenarios of higher education and call on the reader to envision a different kind of higher education and reimagine the contribution of higher education to society, as well as future roles for the IAU. The book will be of interest to higher education policy makers and academics. It is also of interest to the general public, as it provides a comprehensive overview of the challenges higher education institutions currently face and suggests scenarios of what the future of education might look like.